Cardiac Multislice Computed Tomography in the Detection of Phenotypic Polymorphism of Hypertrophic Cardiomyopathy - Mariia O. Tregubova; Kostyantyn V. Rudenko; Svitlana V. Fedkiv; Polina A. Danchenko; Yurii I. Vitkovskyi; Mykhailo S. Ishchenko (Ukrainian Journal of Cardiovascular Surgery, 2022)
Background. Hypertrophic cardiomyopathy (HCM) is an autosomal dominant disease with a prevalence of 1 case per 500 people and is the most common cause of sudden cardiac death in young patients. As clinical manifestations and electrocardiographic data are nonspecific and diverse, noninvasive imaging techniques play a key role in the detection of HCM and the understanding of its pathophysiology.The aim. To evaluate the possibilities of ECG-synchronized cardiac multislice computed tomography (MSCT) as a highly informative diagnostic tool for assessing the morpho-functional state of the heart in patients with HCM.Materials and methods. This was a retrospective analysis conducted at the National Amosov Institute of Cardiovascular Surgery from January 2020 to December 2021. We examined 221 cardiac MSCT scans of patients who underwent the examination to assess the spread of myocardial hypertrophy. Particular attention was paid to the presence of crypts at different levels of the left ventricle (LV), anatomical features of the mitral valve and subvalvular apparatus. The presence of systolic pulling of the anterior mitral valve to the interventricular septum, myocardial mass, LV end-diastolic, LV end-systolic volumes and the corresponding indices of body surface area, ejection fraction were determined and calculated during the functional analysis. Additionally, the anatomy and patency of the coronary arte ries were assessed. The studies were performed on a 640-slice Canon Aquilion One CT scanner with retrospective ECG gating and subsequent image processing. The studies were transferred to a workstation for review and evaluation by a team of radiologists.Results. The mean patient age was 46 ± 23 years, 48% were male. Mean maximal LV wall thickness was 19 mm (range 16–34). In 159 patients (71.9%), there was an asymmetric form of HCM with a predominant thickening of the anterior and anteroseptal segments of the left ventricle at the basal and midventricular levels. Fifty-four (24.4%) patients had symmetric form of HCM. The midventricular form of HCM was detected in 4 patients (1.8%). Apical form of HCM was detected in 3 patients (1.3%). One patient was diagnosed with a tumor-like variant of HCM (0.5%). In 198 patients (89.6%), systolic anterior motion of the mitral valve to the interventricular septum was found. In 95 cases (42.9%), morphological abnormality, abnormality of the number or attachment of the papillary muscles were detected. Forty-eight myocardial crypts were detected in 44 patients (21.7%). In 194 patients (87.7%), patent coronary arteries without signs of stenosis were found, 68 patients (30.7%) had 74 myocardial bridges (33.4%).Conclusions. HCM is a genetic heart disease with enormous phenotypic diversity. Due to its high spatial resolution, cardiac MSCT is an accurate diagnostic tool, which allows to assess the morphofunctional state of the LV, mitral valve, subvalvular apparatus, as well as to analyze the anatomy and narrowing of coronary arteries in patients with HCM.